The Influence of Transformational Leadership Style on Teacher Performance in Coping with High Workloads at SMAN 1 Payakumbuh - Lailatul Fathya; Suci Rahma NioNio (Darul Yasin Al Sys, 2026)
Transformational leadership has become an important issue in educational management, particularly in relation to teacher performance amid increasing professional demands and workload pressures. However, research specifically examining the role of transformational leadership in supporting teacher performance under high-workload conditions in public senior high schools remains limited. This study aims to analyze the effect of transformational leadership style on teacher performance in coping with high workloads at SMAN 1 Payakumbuh. A quantitative approach was employed using an explanatory survey design. The study involved 71 teachers selected through total sampling. Data were collected through questionnaires, observation, and documentation and analyzed using descriptive statistics, normality and linearity tests, and simple linear regression with SPSS. The findings indicate that transformational leadership has a positive and significant effect on teacher performance, as shown by a significance value of 0.000 and an R Square value of 0.141. This result indicates that transformational leadership explains 14.1% of the variance in teacher performance, while the remaining 85.9% is influenced by other factors. This study concludes that transformational leadership plays a meaningful role in strengthening teacher performance under high-workload conditions, although its contribution is relatively limited compared with other potential determinants. Theoretically, this study contributes to educational leadership literature by extending understanding of how principal leadership supports teacher performance in demanding school contexts. Practically, the findings imply that school principals should strengthen transformational leadership practices through clear vision building, professional support, innovation encouragement, and individualized attention to improve teacher performance in public senior high schools.